2020
DOI: 10.1111/gcb.15087
|View full text |Cite
|
Sign up to set email alerts
|

Altered climate leads to positive density‐dependent feedbacks in a tropical wet forest

Abstract: Climate change is predicted to result in warmer and drier Neotropical forests relative to current conditions. Negative density-dependent feedbacks, mediated by natural enemies, are key to maintaining the high diversity of tree species found in the tropics, yet we have little understanding of how projected changes in climate are likely to affect these critical controls. Over 3 years, we evaluated the effects of a natural drought and in situ experimental warming on density-dependent feedbacks on seedling demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 75 publications
(135 reference statements)
3
30
0
Order By: Relevance
“…Decay rates depend on fragmentation efficiency and therefore on soil fauna activity (Sanderman & Amundson, 2003). However, global atmospheric CO 2 and climate change are altering the functioning of all of these trophic levels and of CO 2 dynamics (Allen & Allen, 2017; Allen, Kitajima, & Hernandez, 2014; Allen, Klironomos, Treseder, & Oechel, 2005; Bachelot et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Decay rates depend on fragmentation efficiency and therefore on soil fauna activity (Sanderman & Amundson, 2003). However, global atmospheric CO 2 and climate change are altering the functioning of all of these trophic levels and of CO 2 dynamics (Allen & Allen, 2017; Allen, Kitajima, & Hernandez, 2014; Allen, Klironomos, Treseder, & Oechel, 2005; Bachelot et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The optimal temperature range for pathogen reproduction and infection is likely to explain the contrasting results of our study compared with those of Bachelot et al . ( 2020 ), who found that warming weakened plant–soil feedback. In their study, an increase of 4°C made temperature exceed the upper optimal range and was deleterious to the soil pathogens in the tropics.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a 6‐yr warming experiment showed that increased temperature was a primary driver for the observed increase in foliar pathogen loads in a meadow ecosystem in the Tibet plateau (Liu et al ., 2019 ). Another in situ warming experiment in a wet tropical forest in Puerto Rico reported that the effect of conspecific negative density dependence (CNDD) on seedling survival changed to be positive after 3 yr of warming (presumably due to decreased pathogen pressure or other processes) (Bachelot et al ., 2020 ). This empirical result made the authors suggest that diversity of wet tropical forests could decline under global warming because of the weakening CNDD (Bachelot et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…mortality, productivity and recruitment (Bachelot et al, 2020;Boulanger et al, 2017;Girardin et al, 2016;Kueppers et al, 2017;Kumarathunge et al, 2019;Liang et al, 2017;Liu et al, 2020;Way & Oren, 2010). However, the impact of climate change on forest ecosystems will greatly depend on our actions today and will vary tremendously across biomes and regions (IPCC, 2018).…”
mentioning
confidence: 99%